2009
DOI: 10.1038/jid.2008.245
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Gly573Ser Substitution in TRPV3 on the Development of Allergic and Pruritic Dermatitis in Mice

Abstract: We reported that the Gly573Ser substitution in transient receptor potential vanilloid 3 (TRPV3) led to increased ion channel activity in keratinocytes and caused spontaneous hairlessness in DS-Nh mice. DS-Nh mice also develop allergic and pruritic dermatitis. As the hairless and dermatitis phenotypes were both inherited in an autosomal dominant fashion and could not be segregated from each other, we speculated that TRPV3(Gly573Ser) might be responsible for the dermatitis. Here, we constructed TRPV3(Gly573Ser) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(156 citation statements)
references
References 40 publications
5
151
0
Order By: Relevance
“…Consistent with this idea, a recent report provided evidence that TRPV3, rather than TRPV4, mainly participates in transmission of warm temperature information from keratinocytes to adjacent nerve endings through ATP release (14). It has also been reported that mutation of TRPV3 is linked to defective hair growth and dermatitis in rodents (15,16), although the involvement of TRPV4 has not been confirmed.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Consistent with this idea, a recent report provided evidence that TRPV3, rather than TRPV4, mainly participates in transmission of warm temperature information from keratinocytes to adjacent nerve endings through ATP release (14). It has also been reported that mutation of TRPV3 is linked to defective hair growth and dermatitis in rodents (15,16), although the involvement of TRPV4 has not been confirmed.…”
mentioning
confidence: 48%
“…TRPV3 and TRPV4 (12,13), both of which are expressed in skin keratinocytes, could have distinct roles because they are activated by a similar range of temperatures in the same type of cells. Indeed, TRPV3 is primarily involved in warm temperature-evoked ATP release from keratinocytes (14), and its mutation causes abnormality in hair growth and allergic dermatitis in the skin (15,16). On the other hand, we found that TRPV4, but not TRPV3, associates with the AJ complex (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Noticeably, TRPV3 knock-out causes a wavy hair/curly whisker phenotype and erythroderma (also known as the red man syndrome), indicating that the TRPV3 channel is necessary and important for normal hair morphogenesis and epidermal barrier formation (30). Spontaneous autosomal dominant mutations in TRPV3 that result in constitutive channel activity can also cause hairlessness (31), dermatitis, and inflammatory skin lesions in rodents (32)(33)(34). We have recently identified three genetic gain-of-function mutations located in the S4 -S5 linker and C terminus of TRPV3 that cause Olmsted syndrome, characterized by bilateral multilating palmoplantar keratoderma and periorificial keratotic plaques with severe itching at lesions (35).…”
Section: ␣-Hydroxyl Acids (Ahas)mentioning
confidence: 99%
“…As to TRPV3, G573S, G573C, and W692G substitutions cause the constitutive opening of TRPV3 and lead t o Olmsted syndrome (Lin et al, 2012). G573S and G573C substitutions also have been linked to hair loss and spontaneous dermatitis in mice and rats (Xiao et al, 2008b;Yoshioka et al, 2009). However, amino acid substitutions in TRPV3-ARD have not been reported so far and we have little information about the role of ARD in TRPV3 function.…”
Section: Research Article Protein Cellmentioning
confidence: 99%